Analysis of Obstetric Fistula in Ethiopia - Thankam Sunil; Marguerite Sagna (Tehran University of Medical Sciences, 2009)
Objective: To study the association between social, demographic, cultural and maternal care practice variables and obstetric fistula status in Ethiopia. Materials and Methods: The most recent Ethiopia Demographic and Health Survey conducted in 2005 is used to study the association between social, demographic, cultural and maternal care practice and obstetric fistula. We use both univariate and bivariate analyses to describe the association between the selected variables on obstetric fistula status. Results: A number of social, demographic and maternal care practice variables are found to be significantly (p<0.05) associated with obstetric fistula status. These include level of education, age at first birth, place of residence, antenatal services and place of delivery. Conclusion: The study results emphasize the significance of both treatment and prevention activities in eradicating this highly preventable health condition of women in Ethiopia.